Pore scale investigations on melting of phase change materials considering the interfacial thermal resistance. (June 2020) - Fang, Wen-Zhen; Tang, Yu-Qing; Yang, Chun; Tao, Wen-Quan
Abstract: The performance of phase change materials (PCM) in the latent heat thermal storage system can be improved by doping highly conductive additives to enhance the thermal conduction. In this work, a pore-scale enthalpy-based lattice Boltzmann model is developed to investigate the melting performance of the PCM doped with porous media. The general conjugate boundaries between the doped additives and PCM are properly handled to ensure the continuity of heat flux even when interfacial thermal resistance or local thermal non-equilibrium state cannot be neglected. After code validations, the effects of doping additives on the melting rate of PCM are systematically investigated. The results show that although doping high thermal conductivity additives can enhance the heat conduction, it also significantly reduces the intensity of natural convection. Whether doping additives enhance the melting rate of PCM or not depends on the Rayleigh number and doping content. The melting rate of PCM can be optimized by a proper configuration of doping particles, with a high (low) doping content at the bottom (upper) parts of domain. Furthermore, the interfacial thermal resistance can significantly reduce the melting rate when the ratio of interfacial thermal resistance to bulk conductance resistance is larger than 0.01.